Analysis of Stochastic Predator-Prey Model with Disease in the Prey and Holling Type II Functional Response. (4th September 2020) - Gokila, C.; Sambath, M.; Balachandran, K.; Ma, Yong-Ki
Abstract : A stochastic predator-prey model with disease in the prey and Holling type II functional response is proposed and its dynamics is analyzed. We discuss the boundedness of the dynamical system and find all feasible equilibrium solutions. For the stochastic systems, we obtain the conditions for the existence of the global unique solution, boundedness, and uniform continuity. We derive the conditions for extinction and permanence of species. Moreover, we construct appropriate Lyapunov functions and discuss the asymptotic stability of equilibria. To illustrate our theoretical findings, we have performed numerical simulations and presented the results.